PENDIDIKAN IMAN KATOLIK ANAK DALAM KELUARGA KAWIN CAMPUR BEDA GEREJA DI DEKANAT NIAS KEUSKUPAN SIBOLGA - Gea, Mawarni (Dharmas Education Journal (DE_Journal), 2023)
In the Code of Canon Law, marriage between different churches and different religions is prohibited in the Catholic church. This prohibition does not mean prohibiting people from marrying in different churches. People who wish to marry in a different church must provide a reasonable reason to obtain permission from the local area. Catholics in mixed marriages with different churches. Based on research results found in the field, at first glance it is far from what the church wants. This mixed marriage couple belonging to different churches stated that the moral obligation to pass on the faith according to Catholic beliefs to their children was not successful. To be clear, they made many attempts, but none of them succeeded. In fact, these children did not receive an education based on Catholic beliefs at home, because they were baptized and educated according to Protestant beliefs. Based on the facts above, the church must participate in assisting them to obtain education based on Catholic beliefs. The Church should give serious attention to accompanying and providing pastoral care to mixed-married families. This kind of assistance can be a reinforcement for Catholics to maintain and transmit the faith based on Catholic beliefs to their children.